The level of meeting the quality assurance criteria at Firat University - Ozmen, Fatma; Akdemir, Duygu Arzu (My University, 2013)
In the frame of the Bologna process, the purpose of that study is to reveal the level of implementations of quality assurance required criteria at Fi{dotless}rat University, and to make suggestions for spurring the efforts on quality assessment. Qualitative data analysis through semi-structured interviews conducted with the upper level administrators at Firat University. Whilst the research is limited to Firat University case and is essentially qualitative, the integrated analysis and discussions still provide useful views and suggestions concerning key issues as consequences of implementing the quality assurance criteria within the Turkish higher education system. The results suggest that quality assurance practices are required legal and administrative regulations made within the scope of Council of Higher Education's legislations; the respondents were unsure about the affords for cost and effects of quality assurance in their units; and, despite all the efforts towards integration with the Bologna process, Quality Assurance agencies were not keen in taking into consideration the cultural diversities during auditing and monitoring process. © Sila Science.
Keywords: Accreditation; Bologna process; Higher education; Qualitative research; Quality assurance